Operative Complications and Outcomes Comparing Small and Large Uterine Weight in Case of Laparoscopic Hysterectomy for a Benign Indication - Lambat Emery, Shahzia; Boulvain, Michel; Petignat, Patrick; Dubuisson, Jean (Frontiers in Surgery, 2021)
Study Objective: This study was performed to evaluate the association between uterine weight and operative outcomes in women undergoing laparoscopic hysterectomy for a benign indication. Methods: This is a secondary analysis of a randomized trial with data collected prospectively and retrospectively. The data of 159 women undergoing laparoscopic hysterectomy for a benign indication were analyzed. Women were divided in two groups according to the postoperative uterine weight: small uterus group (< 250 grams) and large uterus group (≥ 250 grams). Operative complications were compared between the 2 groups. Operative outcomes (need for uterine morcellation, operative duration, estimated blood loss), postoperative pain and length of stay were also analyzed. Main results: Operative complications were not significantly different between the two groups (37% in the large uterus group versus 41% in the small uterus group). Operative outcomes showed a significantly increased use of uterine morcellation in the large uterus group (61% in the large uterus group versus 10% in the small uterus group). The operative duration was 150 minutes in the small uterus group and 176 minutes in the large uterus group, which corresponds to an increase of 17%. The mean pain score on the day of surgery was identical in both groups (VAS pain score 5), but significantly in favor of the large uterus group on day 1 postoperatively (VAS pain score 4 in the small uterus group and 3 in the large uterus group). There was no statistical difference between groups in the mean hospital stay (62 +/- 37 hours in the small uterus group group versus 54 ± 21 hours in the large uterus group). In terms of surgical indication, the small uterus group comprised more patients with endometriosis/adenomyosis (36%) and the large uterus group more patients with leiomyoma (93%). Conclusion: The results from this study show that, even if a large uterine weight is associated with increased uterine morcellation requirement and operative duration, a laparoscopic approach is safe and does not increase operative complications nor pain and/or length of hospital stay in women undergoing hysterectomy for a benign indication.